Educational Transformation in the Digital Era: Big Data Analysis to Increase Teacher Management Efficiency in Vocational High Schools - Sari, Maya Novita; Rahman, Arif; Pisol, Mohd Izzuddin Mohd; Herawati, Endang Sri Budi; Rachmawati, Sela; Aprilia, Triana; Fitriana, Destri (Jurnal Akuntabilitas Manajemen Pendidikan, 2023)
Big Data analysis has a role in optimizing the efficiency of teacher management in Vocational High Schools during the educational transformation in the digital era. This research uses a literature review method to analyze relevant concepts, theories, and previous research findings. This research emphasizes vocational schools' challenges, such as the rapid evolution of market-driven skills needs and the lack of qualified vocational teachers. This article proposes a systematic data collection and analysis approach to address these challenges, focusing on volume, velocity, and variability in educational big data. Through a "drivetrain approach," this research outlines a framework for determining purpose, influence, data, and model development, highlighting how this can result in more focused and effective teacher management. The findings show that Big Data analysis can optimize teacher placement based on qualifications, expertise, and school needs, improving teaching effectiveness and overall human resource management efficiency. This article concludes by underscoring the importance of data-based decision-making in the digital era of education.